Atomic-scale evidence of chemical short-range order in CrCoNi medium-entropy alloy. (1st February 2022) - Zhou, Lingling; Wang, Qi; Wang, Jing; Chen, Xuefei; Jiang, Ping; Zhou, Hao; Yuan, Fuping; Wu, Xiaolei; Cheng, Zhiying; Ma, En
Abstract: High (or medium)-entropy alloys (H/MEAs) are complex concentrated solid solutions that may develop chemical short-range order (CSRO). In this regard, CrCoNi, the prototypical face-centered-cubic MEA, has recently kindled a debate in the H/MEA community, as it is uncertain if CSRO can possibly form in such a multi-principal-element solution, where no equilibrium or metastable intermetallic compounds have ever been seen or predicted. To answer this challenging question, here we present firm experimental evidence for the CSRO from electron diffraction as well as atomic-resolution chemical mapping, under an appropriate zone axis. We also develop a methodology to reliably determine the locations of atomic columns from the line scan profiles in the chemical maps, as well as a quantitative covariance-based correlation analysis of the column chemical compositions to reveal the spatial correlations between various atomic pairs. The detailed chemical information affirms the tendency for like-pair avoidance and unlike-pair preference, specifies the preferred atomic packing and plane stacking by the three constituent species, and suggests a proposed atomic configuration that constitutes the CSRO motif. The fraction of CSRO regions is moderately lowered after either plastic deformation or high-temperature heating. A comparison is also made with previous attempts to identify CSROs in H/MEAs. Graphical abstract: Image, graphical abstract